2022
DOI: 10.1186/s40104-022-00683-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drinking water supplementation with Lactobacillus reuteri, and a mixture of reuterin and microcin J25 on the growth performance, caecal microbiota and selected metabolites of broiler chickens

Abstract: Background Since the overuse of antibiotics in animal production has led to a selection of antibiotic-resistant pathogens that affect humans and animals as well. Scientists are therefore searching for novel natural alternatives to antibiotics. In this study Lactobacillus reuteri and a combination of reuterin and microcin J25 (RJ) were evaluated as promoters of growth and modulators of the cecal microbiota and metabolite profiles in broiler chickens. One-day-old Cobb 500 male broilers were distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…234 Here, especially the abundance of benecial bacteria belonging to Lachnospiraceae, Ruminococcaceae, and Lactobacillaceae families were increased as well as the concentrations of short-chain fatty acids. 234 Similarly, the fecal microbiota composition of mice treated with MccJ25 upon gavage was positively modied with an increase in Bidobacterium counts and a decrease in coliform bacteria, which was again accompanied with an increase in short-chain fatty acids. 233 MccJ25 was also able to reduce the non-infectious intestinal inammation in a mouse model of ulcerative colitis (DSSinduced gut inammation) by regulating the gut microbiota in vivo.…”
Section: Reviewmentioning
confidence: 92%
See 3 more Smart Citations
“…234 Here, especially the abundance of benecial bacteria belonging to Lachnospiraceae, Ruminococcaceae, and Lactobacillaceae families were increased as well as the concentrations of short-chain fatty acids. 234 Similarly, the fecal microbiota composition of mice treated with MccJ25 upon gavage was positively modied with an increase in Bidobacterium counts and a decrease in coliform bacteria, which was again accompanied with an increase in short-chain fatty acids. 233 MccJ25 was also able to reduce the non-infectious intestinal inammation in a mouse model of ulcerative colitis (DSSinduced gut inammation) by regulating the gut microbiota in vivo.…”
Section: Reviewmentioning
confidence: 92%
“…229 Supplementation of the drinking water with MccJ25 in combination with reuterin, an antibacterial aldehyde produced by probiotic strains of Lactobacillus reuteri, increased the growth performances of broiler chickens to a similar extent than the use of conventional antibiotics as growth promoters. 234 Concomitantly, the fecal microbiota composition of broilers was modulated and improved. 234 Here, especially the abundance of benecial bacteria belonging to Lachnospiraceae, Ruminococcaceae, and Lactobacillaceae families were increased as well as the concentrations of short-chain fatty acids.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Oral administration of the reuterin supernatant altered the fecal microbiome, decreased heptane and increased 3-methylbutanal in the feces of mice, suggesting the high potential of the reuterin system to relieve some diseases caused by the dysbiosis of intestinal flora [ 23 ]. Oral treatment of broilers with water supplemented with a combination of 5 mM 3-HPA and 0.08 mM microcin J25 promoted growth performance and improved health, presumably through alterations in the cecal microbiome and metabolome, indicating the potential of 3-HPA as a growth promoter instead of as an antibiotic in animals [ 95 ]. Das et al [ 96 ] found that 3-HPA effectively ameliorated iron overload diseases via suppressing hypoxia-inducible factor 2α (HIF-2α), a master transcription factor of intestinal iron absorption, using a high-throughput screen of gut microbial metabolites.…”
Section: Potential Applications Of the Reuterin Systemmentioning
confidence: 99%